2017
DOI: 10.3390/magnetochemistry3010008
|View full text |Cite
|
Sign up to set email alerts
|

New Ethylenedithio-TTF Containing a 2,2,5,5-Tetramethylpyrrolin-1-yloxyl Radical through a Vinylene Spacer and Its FeCl4− Salt—Synthesis, Physical Properties and Crystal Structure Analyses

Abstract: Abstract:To develop novel magnetic conductors exhibiting conducting/magnetic bifunctionalities and peculiar responses to applied magnetic fields, we synthesized new EDT-TTF (ethylenedithiotetrathiafulvalene) donor containing a 2,2,5,5-tetramethylpyrrolin-1-yloxyl radical through a π-conjugated vinylene spacer 1 and examined its electronic and crystal structures, and physical properties. We also prepared its cation radical salts by an electrochemical oxidation method and successfully cleared the crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…In the contribution of Manuel Souto et al [6], a new molecular dyad is reported, based on a monopyrrolo-tetrathiafulvalene electron donor linked by a π-conjugated bridge to a perchlorotriphenylmethyl radical, with interesting properties and the potential to give rise to new radical conductors in the solid state. The combination of radical units with electroactive donor networks is another strategy for preparing magnetic conductors, and in this issue Kazuki Horikiri and Hideki Fujiwara describe charge transfer salts of a new EDT-TTF (ethylenedithiotetrathiafulvalene) donor containing a radical through a π-conjugated vinylene spacer, with diamagnetic GaCl 4 and paramagnetic FeCl 4 anions with strong π-d interactions [7]. Another contribution by Hiroki Akutsu et al describes two dmit-based salts with a stable organic radical-substituted ammonium cation, exhibiting magnetic contributions from segregated 2D anionic and cationic sub-lattices [8].…”
mentioning
confidence: 99%
“…In the contribution of Manuel Souto et al [6], a new molecular dyad is reported, based on a monopyrrolo-tetrathiafulvalene electron donor linked by a π-conjugated bridge to a perchlorotriphenylmethyl radical, with interesting properties and the potential to give rise to new radical conductors in the solid state. The combination of radical units with electroactive donor networks is another strategy for preparing magnetic conductors, and in this issue Kazuki Horikiri and Hideki Fujiwara describe charge transfer salts of a new EDT-TTF (ethylenedithiotetrathiafulvalene) donor containing a radical through a π-conjugated vinylene spacer, with diamagnetic GaCl 4 and paramagnetic FeCl 4 anions with strong π-d interactions [7]. Another contribution by Hiroki Akutsu et al describes two dmit-based salts with a stable organic radical-substituted ammonium cation, exhibiting magnetic contributions from segregated 2D anionic and cationic sub-lattices [8].…”
mentioning
confidence: 99%